BRIDGING MISSION AND PRACTICE: INVESTIGATING THE IMPLEMENTATION OF CHRISTIAN EDUCATIONAL VALUES IN PRIMARY SCHOOLS - Roesmijati Roesmijati (Program Studi PGSD Universitas Flores, 2026)
In Christian primary schools, the school mission plays a central role in shaping both educational goals and classroom practices. The mission reflects a commitment to spiritual, moral, and social development alongside academic achievement. This study aimed to explore how teachers interpret and implement such missions in everyday classroom activities. Conducted in Christian primary schools in Bali, the research employed a mixed-methods design, including surveys, interviews, and classroom observations involving 44 teachers. Data collection tools examined teachers’ perceptions, instructional strategies, and observable integration of Christian values. The results revealed that most teachers actively integrated Christian values such as love, honesty, and forgiveness across subjects, including science and civics, not limited to religious instruction. Daily practices like morning devotions and contextual Bible-based reflections supported students' spiritual growth. Teachers also served as role models, promoting character development through consistent behavior. Challenges identified included curriculum constraints, diverse student religious backgrounds, and the influence of digital culture. Facilitators included strong teacher commitment, institutional support, and collaboration with parents. The findings highlight the effectiveness of mission-aligned pedagogy in fostering students’ moral, social, and spiritual growth. Contributions: This study contributes to values-based education literature by offering empirical insights into how Christian missions can be operationalized in primary classrooms, emphasizing teacher agency, institutional culture, and contextual adaptability.